ELEMEN ARSITEKTUR, INTERIOR DAN SIGNAGE UNTUK MENEMUKAN JALAN DAN BRANDING UNIVERSITAS KRISTEN PETRA - Gunawan Tanuwidjaja; Nerissa Arviana Wijaya; Lavenia Widyanto; Stephanie Seaver Wiarta; John Kenley Sugianto (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2015)
Title: Architectural, Interior Elements and Signage for Wayfinding and Branding in Petra Christian University Petra Christian University (PCU) is a leading private University in Surabaya. PCU possessed advantage in facility?s quality as well as educational service. This was clearly visible in the campus building design that played as architecture, interior and graphic wayfinding elements, especially in W Building (Radius Prawiro Building), EH Building (Entrance Hall) and T Building. Further these elements could also support the University?s Branding and were integrated in the PCU?s integrated wayfinding system.